2013
DOI: 10.2147/copd.s42866
|View full text |Cite
|
Sign up to set email alerts
|

Symptom variability in COPD: a narrative review

Abstract: Chronic obstructive pulmonary disease (COPD) has traditionally been considered an inexorably progressive disease, associated with a constant increase of symptoms that occur as the forced expiratory volume in 1 second (FEV1) worsens, only intermittently interrupted by exacerbations. However, this paradigm has been challenged in recent decades by the available evidence. Recent studies have pointed out that COPD-related symptoms are not consistently perceived by patients in the same way, showing not only seasonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 44 publications
4
56
1
1
Order By: Relevance
“…Several studies have in fact demonstrated that the extent and perception of COPD symptoms are not as stable as previously believed, but show a variability that is not only seasonal, but also weekly and even daily, with symptoms often worsening at night and in the early morning [3, 4]. …”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have in fact demonstrated that the extent and perception of COPD symptoms are not as stable as previously believed, but show a variability that is not only seasonal, but also weekly and even daily, with symptoms often worsening at night and in the early morning [3, 4]. …”
Section: Main Textmentioning
confidence: 99%
“…An example of such “patient-centered” outcomes is given by the circadian variability of COPD symptoms, which has been shown to adversely affect the performance of normal daily activities and to have a substantial negative impact on the quality of life [4]. …”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this traditional paradigm has been contested in recent decades. Several studies have reported that COPDrelated symptoms are not uniformly perceived by patients in a similar manner, showing not just seasonal variation, but also changes in symptom perception over a week or even during a single day (3)(4)(5)(6)(7)(8)(9). This time-dependent variation is of substantial importance, since it has an impact on everyday life activities and health-related quality of life (HRQoL) (5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies suggest that the perception of symptoms may not be as stable as previously suggested. COPD-related symptoms are not consistently perceived by patients in the same way; changes in symptom perception have been observed over the course of a week or even within a single day (5,6), and several approaches have been developed to detect, measure, and manage the variations in the perception of symptoms among COPD patients (7,8).…”
Section: Introductionmentioning
confidence: 99%